2021
DOI: 10.1017/s1049096521000858
|View full text |Cite
|
Sign up to set email alerts
|

Editor Fatigue: Can Political Science Journals Increase Review Invitation-Acceptance Rates?

Abstract: In many political science journals, fewer than half of the invitations sent to potential reviewers are accepted. These low acceptance rates increase workloads for editors and lengthen the review process for authors. This article reports analyses of reviewer invitation acceptance at the Canadian Journal of Political Science between 2017 and 2020. We first describe predictors of invitation acceptance using a coded dataset of almost 1,500 invitations. We find that reviewers who are personally familiar to editors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The literature would suggest that virtually all journal editors struggle to find reviewers with the right expertise for each submitted paper. The proportion of academics who decline to take on reviews is frequently in the range of 30% to 60% (Albert et al, 2016; Djupe, 2015; Fox, 2017; Franceschet et al, 2022; Willis, 2016). There is also some evidence for a declining trend in acceptance rates, with one multijournal study showing 56% of reviewer invitations in 2003 generating a review, compared with just 37% in 2015 (Fox et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature would suggest that virtually all journal editors struggle to find reviewers with the right expertise for each submitted paper. The proportion of academics who decline to take on reviews is frequently in the range of 30% to 60% (Albert et al, 2016; Djupe, 2015; Fox, 2017; Franceschet et al, 2022; Willis, 2016). There is also some evidence for a declining trend in acceptance rates, with one multijournal study showing 56% of reviewer invitations in 2003 generating a review, compared with just 37% in 2015 (Fox et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…I also tried to avoid asking a reviewer too many times in 1 year, to share the load fairly. As past research has shown that an invitation e‐mail with wording individualized to that reviewer also increases the likelihood of a positive response to a review invitation (Franceschet et al, 2022), we reworded the automated journal invitations to be more friendly and less formal. However, despite this, it has become clear that many academics do not have the same approach to reviewing as do I.…”
mentioning
confidence: 99%
“…However, upon reflection, especially when the research pertains to Africa or other underrepresented regions, I consider the potential impact of declining on disseminating valuable insights. Recognising the reviewers’ scarcity and reluctance, editors and authors should be mindful of these challenges and adjust expectations in the academic publishing process (Franceschet et al , 2022; Gupta et al , 2023; Petrescu and Krishen, 2022).…”
Section: The Evolving Landscape Of Peer Reviewmentioning
confidence: 99%
“…Achieving a balance is crucial; the rate at which people submit manuscripts should correspond to their willingness to review. This approach would help address the scarcity issue without compromising the quality of reviews (Franceschet et al , 2022).…”
Section: The Evolving Landscape Of Peer Reviewmentioning
confidence: 99%
“…The available pool of peer reviewers may be further pressurized by invitations to peer review in journals that are not indexed, or possibly even predatory journals [ 24 , 25 ], thinning the available labor and their time, energy and expertise available for indexed and supposedly more scholarly journals [ 26 ]. Peer review may become, as a result, biased because editors might then consistently recruit the same “reliable” (i.e., productive) peer reviewers [ 27 ] or those that are known to the editors [ 28 ]. However, placing the burden on a productive sector of the academic community may result in greater refusals to peer review [ 29 , 30 ].…”
Section: Publons’ Role In Peer Review Rewards: a Critical Perspectivementioning
confidence: 99%